Family Type Relationships and Social Jetlag on The Incident of Hypertension - Handayani, Alya Nurkinasih Putri; Romadhon, Yusuf Alam; Lestari, Nining; Candrasari, Anika (Universitas Muhammadiyah Surakarta, 2023)
Introduction: Hypertension, a disease that is declared a silent killer, often triggers death in society, both globally, nationally and in regions such as Sukoharjo Regency. Knowledge of risk factors or causes can make it easier to control or treat hypertension in the community. There is still limited research discussing the relationship between family type and social jetlag and the incidence of hypertension. Methods: Analyze the relationship between family type and social jet lag on the incidence of hypertension. Observational analytical research with a cross sectional research design using primary data. The research sample consisted of pre-elderly (45-59 years) and elderly (60-69 years). Cluster random sampling was used as a technique to take samples with a total of 66 subjects Results: The results of the Fisher test showed that there was a relationship between positive social jetlag and the incidence of hypertension with a P value < 0.001 with an OR of 72,000. However, there was no relationship between family type and the incidence of hypertension with p 0.680. Conclusion: In conclusion, there is a positive relationship between social jetlag and the incidence of hypertension, but there is no significant relationship between family type and the incidence of hypertension.